Embryonic thermal manipulation improved early immunity in broiler chickens - Amaz, Sadid Al; Poudel, Suman; Pandey, Bal Krishna; Burlakoti, Suresh; Jha, Rajesh; Mishra, Birendra (Frontiers in Physiology, 2025)
Immunity in chickens is age-dependent and develops gradually over time. The initial defense by the host is a crucial mechanism for combating microbial infections. Embryonic thermal manipulation (TM) represents a promising approach for sustainable broiler production. Our previous work provided significant insights into the effects of TM on embryonic thermotolerance, metabolism, growth performance, microbial diversity, and immunity. This follow-up study used a subset of hatchlings previously used in our TM-related studies. This study aims to investigate the effects of TM on immunity-related genes in the spleen, bursa, and thymus. A total of 600 fertile Cobb 500 eggs were incubated for 21 days. After candling, 238 eggs underwent TM at 38.5 °C from embryonic day (ED) 12–18, then transferred to a hatcher at 37.5 °C from ED 19 to 21, while 236 eggs were incubated at 37.5 °C throughout till 21 days. After hatching, 60-day-old unsexed chicks were housed in 12 pens (10 birds/pen, 6 replicates per treatment). The treatments included 1) Control and 2) TM. All birds were raised under standard conditions for the first 21 days. In the spleen, at d 7, the TM group showed significantly lower expression of cytokines (IL-10, IL-12, IL-18), TLRs (TLR-1, TLR-2A, TLR-4, TLR-21), and signaling markers (TBK-1, CD-3, NF-κB, TGF-β, TGF-β3) compared to the Control. At d 21, TM birds exhibited significantly lower (P < 0.05) expression of IL-4, IL-6, IFN-γ, and AvBD-6, while TLR-2A and TGF-β3 were significantly upregulated compared to the Control group. In bursa, at d 7, the TM group showed significantly higher expression of IL-1β, TLR-5, TLR-15, TLR-21, IFN-α, and NF-κB, while IL-6 was significantly downregulated. At d 14, IL-18 was significantly upregulated, and TLR-21 was significantly downregulated in the TM group. At d 21, IL8L1, IL-10, TLR-1, and CD-45 were significantly upregulated, whereas NF-κB expression was significantly downregulated compared to the Control group. In the thymus, at d 14, TLR15 was significantly higher, and at d 21, IL-10 was significantly lower in the TM compared to the Control group. In conclusion, embryonic TM enhanced early immune gene expression in broilers by upregulating essential immune-related genes in the spleen, bursa, and thymus.